PERANCANGAN PHOTOBOOK EKSOTIKA PADANG KOTA LAMA - MUHAMMAD RIDHO, Ir. Drs. Heldi, M.Si., Ph.D., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to explore the historical value and evidence of the heritage of Kejayaang Padang in the Old City so that people are more familiar with and get a visualization of the conditions of the Old Town of the past and present through photography. The design stage starts from data collection, data analysis and design. The process of collecting data from observation, interviews, and documentation. While the process of analyzing data using the 5 W + 1 H. methodThe design of the Padang Kota Lama exotica photobook produced the main media in the form of photobooks arranged in a simple and elegant design style to be easily understood by the reader. This design is also supported by several steps including bookmarks, postcards, stickers, posters, wall clocks, Instagram accounts, and totebags which play a role in supporting the main media and promotional media.